INTERVENTION MODEL OF DECUBITUS PREVENTION USING BRANDEN SCALE METHOD TO DECREASE THE DECUBITUS RISK DEGREE IN STELLA MARIS HOSPITAL MAKASSAR - ELMIANA BONGGA LINGGI (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2019)
Decubitus is a serious problem because of ulcer incident. The way how to reduce pressure the ulcer problem is to provide a preventive intervention of decubitus. To determine of decubitus interventions to the patient, it needed an assessment of risk pressure ulcer. Braden Scale is the type of scale used in assessing the risk of pressure ulcer in the patient with a long bed rest. This study aimed to determine the differences in the degree of risk pressure before and after administration of decubitus prevention in the treatment room of Stella Maris Makassar Hospital. This study used a pre-experiment with the approach of the one group pre test-post design. Sampling was done by non-probability sampling technique, used consecutive sampling approach with specimen of 15 patients. Data collection instruments such as pressure ulcer risk assessment was the Braden Scale methods. The result of statistical test Wilcoxon concluded that value p = 0,014 obtained level ? = 0,05. There were significant differences the degree of risk pressure ulcer before granting intervention in the treatment room of Stella Maris Makassar Hospital.